2014
DOI: 10.1104/pp.114.247205
|View full text |Cite
|
Sign up to set email alerts
|

Broad 4-Hydroxyphenylpyruvate Dioxygenase Inhibitor Herbicide Tolerance in Soybean with an Optimized Enzyme and Expression Cassette  

Abstract: With an optimized expression cassette consisting of the soybean (Glycine max) native promoter modified for enhanced expression driving a chimeric gene coding for the soybean native amino-terminal 86 amino acids fused to an insensitive shuffled variant of maize (Zea mays) 4-hydroxyphenylpyruvate dioxygenase (HPPD), we achieved field tolerance in transgenic soybean plants to the HPPD-inhibiting herbicides mesotrione, isoxaflutole, and tembotrione. Directed evolution of maize HPPD was accomplished by progressivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
80
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 52 publications
1
80
0
Order By: Relevance
“…Tobacco, a dicot species, is highly sensitive to mesotrione, however, when transformed with a HPPD gene from wheat, showed tolerance to this herbicide (Hawkes et al, 2001). Transgenic soybeans tolerant to mesotrione, tembotrione, and isoxaflutole have been developed with an herbicide-insensitive maize HPPD to increase the selectivity and spectrum of weed control (Siehl et al, 2014). Mesotrione and other HPPD-inhibitors are important in controlling several ALS- and PS II-inhibitor resistant weed biotypes (Sutton et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco, a dicot species, is highly sensitive to mesotrione, however, when transformed with a HPPD gene from wheat, showed tolerance to this herbicide (Hawkes et al, 2001). Transgenic soybeans tolerant to mesotrione, tembotrione, and isoxaflutole have been developed with an herbicide-insensitive maize HPPD to increase the selectivity and spectrum of weed control (Siehl et al, 2014). Mesotrione and other HPPD-inhibitors are important in controlling several ALS- and PS II-inhibitor resistant weed biotypes (Sutton et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Herbicide tolerance is typically assessed by comparing the inhibition of wild type and mutant HPPD proteins by different inhibitors. A range of different mutations has been proposed for HPPD proteins in mousear cress, rice, and soybean . Recently, Siehl et al presented an approach to develop transgenic soybean plants tolerant to a variety of HPPD inhibitors by directed evolution of maize HPPD .…”
Section: Introductionmentioning
confidence: 99%
“…These mutations did not involve any residues reported to be related to catalytic function . The authors concluded that the improved herbicide tolerance occurred “through the accumulated effect of many small changes outside the active site that influence the catalytic properties of the enzyme in a manner that is not obvious upon inspection of the structure.” Hence, a detailed understanding of the molecular phenomena promoting herbicide tolerance and especially the effect of mutations outside of the active site is lacking to date.…”
Section: Introductionmentioning
confidence: 99%
“…Given this scenario, reduced catabolism of homogentisate in MO12 cells would therefore increase the effective levels of homogentisate for translocation into plastids for tocochromanol production. However, it was recently reported that homogentisate can be synthesized in the plastids of soybean and likely other legumes as well (Siehl et al, 2014). This would indicate that leguminous plants can utilize plastidic homogentisate directly for secondary metabolism without necessitating transport into the plastids, as is the case in other plants.…”
Section: Discussionmentioning
confidence: 99%